2014
DOI: 10.1186/1477-7827-12-42
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of the pluripotency markers sex-determining region Y-box 2 and Nanog homeobox in ovarian endometriosis

Abstract: BackgroundThe precise etiology of endometriosis is not fully understood; the involvement of stem cells theory is a new hypothesis. Related studies mainly focus on stemness-related genes, and pluripotency markers may play a role in the etiology of endometriosis. We aimed to analyze the transcription pluripotency factors sex-determining region Y-box 2 (SOX2), Nanog homeobox (NANOG), and octamer-binding protein 4 (OCT4) in the endometrium of reproductive-age women with and without ovarian endometriosis.MethodsWe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 31 publications
2
24
1
Order By: Relevance
“…In recent years, molecular mechanisms have been proposed to explain the pathogenesis of endometriosis. It has been suggested that aberrant gene expression in the endometrium may contribute to the etiology of endometriosis (Laudanski, Charkiewicz, & Kuzmicki, ; McKinnon, Bertschi, & Wotzkow, ; Poncelet, Leblanc, & Walker‐Combrouze, ; Song, Xiao, & Fu, ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, molecular mechanisms have been proposed to explain the pathogenesis of endometriosis. It has been suggested that aberrant gene expression in the endometrium may contribute to the etiology of endometriosis (Laudanski, Charkiewicz, & Kuzmicki, ; McKinnon, Bertschi, & Wotzkow, ; Poncelet, Leblanc, & Walker‐Combrouze, ; Song, Xiao, & Fu, ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, molecular concepts have been introduced to explain the pathogenesis of endometriosis. It has been reported that aberrant gene expression in endometrium of women may contribute to the etiology of endometriosis [2][3][4][5] .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the finding of cells displaying germ cell-specific DDX4 and IFITM3 proteins suggests an ovarian origin, and as far as we could track in the literature this is the first evidence reported for ovarian-sourced cells in the endometrioma. In line with this, expression of pluripotency markers such as OCT4 and NANOG and the protoncogene c-KIT in stem-like cells in endometriosis have been described and related to the development of the disease and progression towards ovarian cancer [ 9 , 21 ]. Nevertheless, the presence of ovarian germ line stem cells as contributors to endometriosis progression remains to be further studied through functional analysis in isolated DDX4/IFITM3-positive cells.…”
Section: Discussionmentioning
confidence: 91%